Engineering magnetic domains in manganite thin films by laser interference - Lin, W. (2013)
We report on the laser interference (LI) aided conversion from maze-like to stripe-like magnetic domains in La1−xSrxMnO3 (x ∼ 0.3) thin films grown on LaAlO3 substrates. This conversion is attributed to the periodic, local, and rapid heating by LI which facilitates the reconfiguration of magnetic domains without damaging the film structures. By annealing the sample, the stripe-like domains can be converted back to the maze-like state. Our result represents a non-magnetic scheme for reversible magnetic domain engineering in ferromagnetic thin films.